Numerical cooking for pasteurized soft boiled eggs - Jenko, Marjan (Strojniški vestnik, 2015)
The industrial preparation of pasteurized soft boiled eggs requires meticulous planning of the thermal process. Requirements on keeping the yolk liquid and on extinction of potential salmonella allow little leeway in the creation of this process. The variation of the eggs' properties adds to complexity. Thermal simulation of heat transfer within an egg is needed to get correlation data between transient temperature distribution and the egg's dimensional and material properties. A simulator of conductive heat transfer with fixed grid of cells is developed for this purpose. Firstly, the essentials of the computational algorithm with fixed grid of cells are presented on a one dimensional heat transfer problem. Secondly, the algorithm is enhanced for a two dimensional thermal simulation which is implemented in the thermal simulator of an egg. The simulated volume is a cylinder. The simulated object (the egg) is defined within the cylinder. Simulation results are analysed and used in the creation of the thermal process which results in certified pasteurized soft boiled eggs. The presented approach to the design of simulation can be used for applications ranging beyond the thermal simulation of foods. It can be adjusted for any simulation where local energy flow is a function of specific gradients. Numerical simulation with a fixed grid of cells adds to the computing requirements but reduces the programming effort to a manageable level when developing a custom simulation tool.
Keywords: Fourierov zakon toplotnega toka; jajca; predelava živil; simulacija prenosa toplote; simulacije s fiksno mrežo; toplotne simulacije